PENGARUH PRICE EARNING RATIO (PER), RETURN ON EQUITY (ROE) DAN MARKET TO BOOK VALUE OF EQUITY (MBVE) TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2018-2022 - Laila Badriah; Vega Anismadiyah (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of price earning ratio, return on equity and market to book value of equity on stock returns in food and beverage companies listed on the IDX for the 2018-2022 period. In this research there are three independent variables, namely price earning ratio, return on equity and market to book value of equity and one dependent variable, namely stock returns. The sample method used was a purposive sampling method, the population found in this research was forty companies with a sample size of five companies that met the criteria. The data used is secondary data obtained from www.idx.co.id and also the official website of each company in the form of the company's annual financial report. This research analysis uses multiple linear regression, then for testing in multiple linear regression research using Eviews 12 SV (x64) software using the t test (Partial) and f test (Simultaneous). Based on the research results, it shows that: partially PER (X1) has a significant effect on stock returns (Y), partially ROE (X2) has a significant effect on stock returns (Y), partially MBVE (X3) has a significant effect on stock returns (Y) , and simultaneously PER, ROE and MBVE have a significant effect on stock returns.